THE SEPARATION THESIS AND H. L. A. HART’S LEGAL POSITIVISM - Chang, Frank (REVISTA PARADIGMA, 2020)
The article aims to analyze Hebert Hart’s legal philosophical thought, mainly with regard to the relationship between law and morality, proceeding to discuss the various criticisms that were made to his theory, in order to finally conclude on the foundations of his concept of law and its understanding of the place of morality in relation to law.